Asians on campus: understanding the Asian Americans' experience and struggles in higher education - Moy, Eric (Kansas State University, 2013)
The college environment is often made up of a variety of people, fulfilling various roles throughout the campus climate. There are students, staff members, faculty, and administration. In examining the roles, students of Asian ancestry make up a part of a sub-category of students. In a campus population where students of different ethnic backgrounds come together to receive an education, Asian students have remained one of the minorities on a college campus. Even with a growing presence on campus, Asian American students have often been faced with additional struggles that their non-minority student counterparts face. The report will include a wide range of literature review looking at the different theoretical models, foundations, and outlines of ethnic identity development in higher education. The purpose of the report is to provide an outline of the different experiences of Asian Americans during their time at a university. The report will also acknowledge the differences, while drawing on similarities, to discuss potential outcomes for minority students. The final section of the report will include a review of recommendations and best practices for student affairs to implement in their work with Asian American students.
Keywords: Asian American; Higher education; Struggles; Experience; Chickering; Blumer; Asian American Studies (0343); Asian Studies (0342); Higher Education (0745)